Burden of advanced breast cancer for patients and caregivers in Europe: comparison of two treatment forms of vinorelbine, oral and intravenous. (1st November 2016) - Barni, Sandro; Freier, Beata; Garau, Isabel; Mouysset, Jean-Loup; Sediva, Marcela; Zamagni, Claudio; Berdeaux, Gilles; de Almeida Agudo, Cecilia
Abstract: Aim: To assess the burden of disease associated with advanced breast cancer (ABC) treated with oral (VinO) or intravenous vinorelbine (VinIV) from the perspective of patients and caregivers in five European countries. Methods: This was an observational, prospective, international, multicenter study. Patients were included in the study at the beginning of their second cycle of chemotherapy with vinorelbine and categorized into two groups depending on whether they received VinO or VinIV. At baseline (V0) and at the end of the second cycle of chemotherapy (V1), patients and caregivers were asked to complete self-administered questionnaires: SF-12 and burden of disease. Results: At baseline, the two groups were well balanced in demographic and clinical characteristics. However, while HER2+ (human epidermal growth factor receptor 2) disease was significantly more frequent in patients receiving VinIV, patients receiving VinO were predominantly treated with single-agent therapy and were older than those treated with VinIV (67.1 years versus 57.7 years [ p  = 0.05]). As measured with SF-12, patients with VinO had, at end of cycle 1 and end of cycle 2, significantly more favorable outcomes in physical summary score, role physical, role emotional and mental health (all p  < 0.05) than those treated with VinIV. Trends for a better caregiver mental score and social functioning were also observed with VinO (cycle 1 and 2; p  < 0.10). From a patient perspective, no major difference was reported on the burden of disease between the two groups, however, a trend for a better" overall impact on daily life" was observed in VinO patients. Major significant differences, showing a lower burden of disease with VinO, were also reported from caregivers. In addition, in patients treated with VinO, mental score was almost similar to the one of the general population. Conclusion: VinO showed benefits over VinIV for both patients and caregivers, particularly in health related quality of life and burden of disease. Because of its observational design, results are only informative.